Impaired secretion of interferons by dendritic cells from aged subjects to influenza: Role of histone modifications - Prakash, Sangeetha (Springer Netherlands, 2012)
Increased susceptibility to respiratory infections such as influenza is the hallmark of advancing age. The mechanisms underlying the impaired immune response to influenza are not well understood. In the present study, we have investigated the effect of advancing age on dendritic cell (DC) function because they are critical in generating robust antiviral responses. Our results indicate that monocyte derived DCs from the aged are impaired in their capacity to secrete interferon (IFN)-I in response to influenza virus. Additionally, we observed a severe reduction in the production of IFN-III, which plays an important role in defense against viral infections at respiratory mucosal surfaces. This reduction in IFN-I and IFN-III were a result of age-associated modifications in the chromatin structure. Investigations using chromatin immunoprecipitation with H3K4me3 and H3K9me3 antibodies revealed that there is increased association of IFN-I and IFN-III promoters with the repressor histone, H3K9me3 in non-stimulated aged DCs compared to young DCs. This was accompanied by decreased association of these promoters with activator histone, H3K4me3 in aged DCs after activation with influenza. In contrast to interferons, the association of TNF-alpha promoter with both these histones was comparable between aged and young subjects. Investigations at 48 h suggested that these changes are not stable and change with time. In summary, our study demonstrates that myeloid DCs from aged subjects are impaired in their capacity to produce IFNs in response to influenza virus and that age-associated altered histone expression patterns are responsible for the decrease in IFN production. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11357-012-9477-8) contains supplementary material, which is available to authorized users.